Atherosclerosis and its impact on the outcomes of patients with deep venous thrombosis - Keller, Karsten; Prochaska, Jürgen; Coldewey, Meike; Göbel, Sebastian; Schmitt, Volker H.; Hahad, Omar; Ullmann, Alexander; Nagler, Markus; Lamparter, Heidrun; Espinola-Klein, Christine; Münzel, Thomas; Wild, Philipp (Life, 2022)
Introduction: Atherosclerosis and pulmonary embolism (PE) affect cardiovascular mortality substantially. We aimed to investigate the impact of atherosclerosis on the outcomes of patients with deep venous thrombosis (DVT) and to identify the differences in DVT patients with and without PE. Methods: Patients with DVT with and without symptomatic atherosclerosis (defined as coronary artery disease, myocardial infarction and/or peripheral artery disease) as well as with and without PE under oral anticoagulation were enrolled during January 2011-April 2013 and compared. The impact of symptomatic atherosclerosis on several outcomes was analyzed. Results: Overall, 509 DVT patients (70.0 [56.0-77.0] years, 51.9% females) were included in this study. Among them, 179 (36.3%) had symptomatic atherosclerosis and 204 (40.1%) a concomitant PE. DVT patients with symptomatic atherosclerosis were older (74.0 [IQR 65.0-80.0] vs. 63.0 [48.0-75.0] years, p < 0.0001), more often male (56.4% vs. 43.9%, p = 0.0087) and had a higher prevalence of classical CVRF and a higher Charlson comorbidity index (7.00 [5.00-8.00] vs. 4.00 [2.00-6.00], p < 0.001). Symptomatic atherosclerosis was associated with increased mortality (HR 1.98 [95%CI 1.12-3.49], p = 0.018) and hospitalizations (HR 1.64 [95%CI 1.21-2.21], p = 0.0012) and primary long-term outcome (HR 1.99 [95%CI 1.31-3.04], p = 0.0013) during the 2 years follow-up-period in DVT patients. DVT patients without PE had diabetes mellitus (28.2% vs. 16.3%, p < 0.01) and symptomatic atherosclerosis (42.9% vs. 26.4%, p < 0.001) more often compared to DVT patients with PE, and symptomatic atherosclerosis was associated with isolated DVT (without PE) (OR 2.01 [95%CI 1.28-3.16], p < 0.01). Conclusions: Atherosclerosis was associated with isolated DVT (without PE) and increased mortality in DVT patients under oral anticoagulation. The profile of CVRF and comorbidities differed between DVT patients with and without a concomitant PE. In the case of DVT or PE, patients should be screened for concomitant atherosclerotic disease. Clinical Trial Registration: at clinicaltrials with Unique identifier NCT01809015.
This article belongs to the special issue "Vascular disease: etiologic, diagnostic, prognostic and therapeutic research"
Gesehen am 13.07.2022